Using the Protein Leverage Hypothesis to understand socioeconomic variation in obesity - Bekelman, Traci A. (2017)
The protein leverage hypothesis (PLH) predicts that protein appetite will stimulate excess energy intake, and consequently obesity, when the proportion of protein in the diet is low. Experimental studies support the PLH, but whether protein leverage can be used to understand socioeconomic (SES) variation in obesity is unknown. The objective of this study was to test two hypotheses from the PLH under non-experimental conditions. Consistent with the PLH, we expect that (1) absolute protein intake will be similar across populations, here defined as SES groups and, (2) the proportion of protein in the diet will be inversely associated with energy intake.